Особливості формування та використання ресурсного потенціалу торговельних підприємств в Україні - Краснокутська, Наталія Станіславівна; Круглова, Олена Анатоліївна (Інститут трансформації суспільства, 2016)
У статті представлено результати емпіричного дослідження динаміки, структури та ефективності використання ресурсного потенціалу торговельних підприємств України. Визначено, що за 2010–2015 рр. ресурсний потенціал торгівлі збільшився на 62,6%. Доведено, що найбільшу значущість для торговельних підприємств мають товарний і фінансовий потенціал, питома вага якого у складі ресурсних можливостей торгівлі за періодами часу становила 14,7–19,3% та 61,8–63,5% відповідно. За 2010–2015 рр. діагностовано зниження потенціаловіддачі та рентабельності ресурсного потенціалу в торгівлі.

Introduction. Resource potential ensures the effectiveness of operation and development of trade enterprises, their competitive position and investment appeal, as well as the possibility of creating specific value for customers, owners and other economic agents. Misunderstanding of industry features of the formation of resource potential and ignoring trends of its development during substantiation and implementation of corporate strategy are some of the problems of strategic management. Purpose. The diagnostic results of resource potential of trade enterprises which are based on the size, dynamics, structure and efficiency of the use of resource potential of trade enterprises in Ukraine are presented in this research paper. Methods.While evaluating the formation and implementation of resourse potential of trade enterprises, the authors used statistical monitoring, as well as dynamic, comparative and structural analyses. Results. The research results (2010-2015) show that there was a growth of the resource potential of trade enterprises in Ukraine estimated at 62.6%, including growth of commodity potential equal to 113.1%, technical potential - 26.9% human resources potential - 54.8%, financial potential - 61.9%. It was established that a significant proportion in resource potential was represented by commodity (14.7-19.3%) and financial (61.8-63.5%) potentials. The authors of the article have identified the advantages of the use of resource potential and compared them with the relevant advasntages of enterprises of other types. It has been proved that ensuring the profitability of trade enterprises while managing resource potential is one of the problematic areas. Conclusions. The research undertaken revealed trends in the development of resource potential of trade enterprises in Ukraine. The trends should be taken into account when identifying the key determinants to success and planning a strategy to develop trade enterprises in modern economic conditions.
Particularities of formation and use of resource potential of trade enterprises in Ukraine
Keywords: підприємства торгівлі; структура; потенціаловіддача; матеріальний потенціал; resource potential; trade enterprises; structure; use of resource potential; potential return